2022
DOI: 10.1097/prs.0000000000008818
|View full text |Cite
|
Sign up to set email alerts
|

Surgery-First Orthognathic Approach to Correct Facial Asymmetry: Artificial Intelligence–Based Cephalometric Analysis

Abstract: Background: The surgery-first orthognathic approach has been applied at our institution since 2007. However, its indications remain debated. The aim of this study was to investigate the reliability of the surgery-first approach to correct facial asymmetry compared to the traditional orthodontics-first approach using a novel artificial intelligence–based cephalometric analysis. Methods: Intervention outcomes of surgery-first (n = 33) and orthodontics-first (n = 26) approaches to correct facial asymmetry were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
(12 reference statements)
0
15
0
Order By: Relevance
“…In combination with human skills, AI promises to be the most useful and valuable tool in the everyday practice of oral and maxillofacial surgery [ 102 ], similarly to modern medical imaging methods, such as variations based on computed tomography (CT), CBCT, and magnetic resonance imaging (MRI), which have transformed how clinicians visualize facial anatomy and pathology [ 103 ]. Representative articles are already reporting on AI algorithms aiding in diagnosis, therapeutic decision making, preoperative planning, and prediction and evaluation of outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In combination with human skills, AI promises to be the most useful and valuable tool in the everyday practice of oral and maxillofacial surgery [ 102 ], similarly to modern medical imaging methods, such as variations based on computed tomography (CT), CBCT, and magnetic resonance imaging (MRI), which have transformed how clinicians visualize facial anatomy and pathology [ 103 ]. Representative articles are already reporting on AI algorithms aiding in diagnosis, therapeutic decision making, preoperative planning, and prediction and evaluation of outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Overall care of the orthodontic patient, from determining the movement of the teeth to communication, guidance, and telemedicine, is possible using AI [ 49 , 91 , 92 , 93 , 94 , 95 ]. The literature research also showed that the scale of AI-affected orthodontic subfields is extensive, ranging from pre-treatment AI monitoring, through AI growth/aging 3D morphological predictions and virtual treatment planning [ 59 , 85 , 103 , 195 ] with later in-treatment decision-making, monitoring, and patient management, to post-treatment evaluation and retention monitoring [ 196 , 197 ]. In-office treatment personalization by means of 3D printed customized devices easily designed with the support of AI is possible in the future with current AI implementation trends, although this is yet to be realized [ 97 , 98 , 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advancements in the mechanics of tooth movements, stability of specific skeletal movements in the context of rigid fixation and understanding of the effects of surgery on tooth movement have allowed for the introduction of several different approaches to address skeletal dysplasia, including surgery-first and surgery-only approaches, as well as the use of clear orthodontic aligners in lieu of conventional metal braces. In appropriately selected patients, these protocols each offer several benefits, including reduced treatment time, greater quality of life, and improved patient satisfaction [26][27][28][29].…”
Section: Surgery First/surgery Only/clear Aligner Therapymentioning
confidence: 99%
“…1 It enables to improve the overall facial esthetics and harmonize the facial profile, in addition to correcting malocclusion. 2 Sagittal split ramus osteotomy (SSRO) of the mandible is the mainstay of modern orthognathic surgery, which allows wide bony contact between the osteotomized segments, rendering better stability and better results at a lower risk of pseudarthrosis. 3 However, neurosensory disturbance of the inferior alveolar nerve (IAN) remains a common sequela after SSRO.…”
mentioning
confidence: 99%
“…Orthognathic surgery has been proven to be highly effective in the treatment of a wide spectrum of maxillofacial deformities 1 . It enables to improve the overall facial esthetics and harmonize the facial profile, in addition to correcting malocclusion 2 . Sagittal split ramus osteotomy (SSRO) of the mandible is the mainstay of modern orthognathic surgery, which allows wide bony contact between the osteotomized segments, rendering better stability and better results at a lower risk of pseudarthrosis 3 .…”
mentioning
confidence: 99%